The conditional stock market response to banks' distressed asset sales on CDS availability. Issue 56 (1st December 2020) - Kiesel, Florian; Manz, Florian; Schiereck, Dirk
ABSTRACT: This paper analyzes the stock market feedback on bank announcements of non-performing loan (NPL) sales, conditional on whether credit default swaps (CDS) are traded on the vendor bank's debt or not. Using a sample of 259 NPL sale announcements from 2012–2018, we find that NPL sales are related to positive abnormal stock returns if there is no CDS trading on the vendor bank's debt. In contrast, if a CDS on the bank's debt is outstanding, we find a negative stock market reaction. Similarly, we provide evidence that the positive market reaction is muted for banks that are considered too-big-to-fail. While the regulator currently strengthens NPL sales, our results provide evidence that CDS trading reassigns banks' risk exposure.